2021
DOI: 10.1038/s41467-021-21372-4
|View full text |Cite|
|
Sign up to set email alerts
|

Cell non-autonomy amplifies disruption of neurulation by mosaic Vangl2 deletion in mice

Abstract: Post-zygotic mutations that generate tissue mosaicism are increasingly associated with severe congenital defects, including those arising from failed neural tube closure. Here we report that neural fold elevation during mouse spinal neurulation is vulnerable to deletion of the VANGL planar cell polarity protein 2 (Vangl2) gene in as few as 16% of neuroepithelial cells. Vangl2-deleted cells are typically dispersed throughout the neuroepithelium, and each non-autonomously prevents apical constriction by an avera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 113 publications
4
34
0
2
Order By: Relevance
“…However, the biological mechanisms underlying this developmental anomaly and associated cutaneous stigmata are not well understood and may be under-reported due to inherent challenges in resolving these genetic events. Post-zygotic variation, including single nucleotide changes and copy number alteration, has been described in planar cell polarity genes in association with open neural tube defects (Tian et al 2020;Galea et al 2021). Such findings support that somatic mosaicism may serve as a mechanism of disease.…”
Section: Discussionmentioning
confidence: 65%
“…However, the biological mechanisms underlying this developmental anomaly and associated cutaneous stigmata are not well understood and may be under-reported due to inherent challenges in resolving these genetic events. Post-zygotic variation, including single nucleotide changes and copy number alteration, has been described in planar cell polarity genes in association with open neural tube defects (Tian et al 2020;Galea et al 2021). Such findings support that somatic mosaicism may serve as a mechanism of disease.…”
Section: Discussionmentioning
confidence: 65%
“…With respect to congenital abnormalities such as NTDs, the existing literature concerning any association between somatic variants with the development of an NTD is quite limited. Galea et al (2018Galea et al ( , 2021 reported that a somatic Vangl2 deletion in murine neuroepithelial cells as well as in surface ectodermal cells causes SB in mice. In our recent publication, we described somatic variants in some key PCP genes (e.g., VANGL1 and FZD6) in neural tissue that are associated with human NTDs, suggesting a potentially important role somatic variants can play in the occurrence of human NTDs (Tian et al, 2021).…”
Section: Human Ntd Associated Gene Variants Can Be Germline or Somaticmentioning
confidence: 99%
“…Closure is a complex, coordinated, dynamic process in which active multi-scale cell-generated forces exceed residual tissue stresses to produce tubular morphogenesis (6)(7)(8)(9). Genetic or teratogenic disruptions of neural tube closure biomechanics can cause neural tube defects (10,11). Although essential, the analysis of morphogenetic forces generated during vertebrate neural tube closure has not yet been possible.…”
Section: Introductionmentioning
confidence: 99%